Relationship between green bonds and carbon neutrality: evidence from top five emitting countries’ sectoral CO2 emissions - Ugur Korkut Pata; Mustafa Tevfik Kartal; Zahoor Ahmed; Avik Sinha (Financial Innovation)
Abstract This study analyzes the influence of green bonds on carbon neutrality. It examines the daily data of sectoral CO2 emissions of the top five CO2-emitting nations from January 2, 2019 to December 30, 2022 using wavelet transform coherence, quantile-on-quantile regression, Granger causality in quantiles, and quantile regression approaches. The results revealed that (i) green bonds are strongly related to sectoral CO2 emissions; (ii) green bonds reduce transport sector CO2 emissions in China, the US, and Japan while causing an upsurge in India and Russia; (iii) green bonds reduce industrial sector CO2 emissions only in the US; (iv) green bonds have a declining influence in energy sector CO2 emissions at lower quantiles in India, China, and the US, whereas the impact increases at higher quantiles; and (v) green bonds decrease residential sector CO2 emissions in the US, Russia, and Japan. The study revealed that green bonds help reduce CO2 emissions in the residential sector in various quantiles. Therefore, the US, Russia, and Japan should raise household awareness of green energy utilization by promoting them with green bonds. In addition, green bonds can effectively reduce transportation sector CO2 emissions in China and the US. Therefore, the policymakers of the two global powers should contribute to global CO2 reduction by promoting green transportation and clean energy transition in the transportation sector through green bonds. Thus, green bonds can play an effective role in the fight against global warming.